Artist - Author : Contemporary Artists' Books. - Weatherspoon Art Gallery, Greensboro; The Emerson Gallery, Clinton; Museum of Contemporary Art, Chicago; Lowe Art Museum, Coral Gables; Western Gallery, Bellingham; University Art Gallery, Amherst; Lauf, Cornelia; O'Brien, Glenn; Padon, Thomas; Phillpot, Clive; Polo, Jane; Rattazzi, Serena; et al. (New York : The American Federation of Arts, 1998)
Abeles, Kim ; Acker, Kathy ; Alatalo, Sally ; Baldessari, John ; Barrow, Amanda ; Bié, Jérôme Saint-Loubert ; Bloom, Barbara ; Boltanski, Christian ; Bonin, Cosima von ; Brecht, George ; Bruly-Bouabré, Frédéric ; Burns, Gaty Panter & Charles ; Bürobert ; Cha, Theresa Hak Kyung ; Clegg & Guttmann ; Cranston, Meg ; Cutts, Simon ; Darboven, Hanne ; Dion, Mark ; Ehrenberg, Felipe ; Farrell, Seamus ; Finlay, Ian Hamilton ; Fischli & Weiss ; Freeman, Brad ; Gigli, Romeo ; Gillick, Liam ; Goldin, Nan ; Goldstein, Gary ; Green, Renée ; Guerrilla Girls ; Gursky, Andreas ; Hart, Claudia ; Hastings, Pattie Belle ; Hirsch Farm Project ; Hohenbüchler, Christine & Irene ; Holzer, Jenny ; Jaar, Alfredo ; Kabakov, Ilya ; Kahn, Robin ; Karan, Donna ; Katz, Leandro ; King, Ron ; Kippenberger, Martin ; Komar & Melamid ; Koons, Jeff ; Kosuth, Joseph ; Kruger, Barbara ; Kuper, Yuri ; Landers, Sean ; Laxson, Ruth ; LeWitt, Sol ; Leccia, Ange ; Levine, Sherrie ; Lovejoy, Margot ; Lum, Ken ; Lum, M.M. ; Martins, Ross ; Material, Group ; McCarney, Scott ; Müller, Christian Phillip ; Müller, Regina ; Nannucci, Maurizio ; Oehlen, Albert ; Osborn, Kevin ; Parker, Cornelia ; Parreno, Philippe ; Pawson, Mark ; Peress, Gilles ; Philips, Tom ; Piper, Adrian ; Prina, Stephen ; Prince, Richard ; Robbins, David ; Roiter, Andrei ; Rosbotham, Lyle ; Roth, Dieter ; Sligh, Clarissa ; Soesemann, Davi Dei Hompson & Petra ; Steinbach, Haim ; Stokes, Helen Douglas & Telfer ; StopOver Press ; The Paper Tiger Television Collective ; Tilson, Jake ; Tremlett, David ; Trockel, Rosemarie ; Voss, Jan ; Wall, Jeff ; Wegman, William ; Weiner, Lawrence ; Wewerka, Stefan ; White, Pae ; Williams, Christopher ; Zobernig, Ferdinand Schmatz & Heimo ; Zubell, Francine ; van Horn, Erica
Artist - Author : Contemporary Artists' Books, Weatherspoon Art Gallery, Greensboro, February 8 - April 12, 1998 / The Emerson Gallery, Clinton, August 31 - October 18, 1998 / Museum of Contemporary Art, Chicago, November 6, 1998 - January 3, 1999 / Lowe Art Museum, Coral Gables, February 18 - April 14, 1999 / Western Gallery, Bellingham, April 30 - June 27, 1999 / University Art Gallery, Amherst, October 29 - December 18, 1999
Engels
boek